The soul of leadership unlocking your potential for greatness - Chopra, Deepak (Harmony Books, 2010)
"The Soul of Leadership" decodes the mysterious qualities that have propelled history's greatest leaders to the top of the ranks and shrouded them in legend -- Gandhi, Martin Luther King, Winston Churchill, Buddha -- and provides a hands-on approach to understanding and mastering these qualities.